TINGKAT PEMAHAMAN MASYARAKAT TENTANG PASAR MODAL SYARIAH DI SULAWESI SELATAN - Muhammad Nur Abdi; Agusdiwana Suarni (AkMen JURNAL ILMIAH, 2019)
Makassar city with various professions, gender, educational backgrounds as well as ethnic and religious groups, makes various understandings about the Islamic capital market. The purpose of this study is to determine the level of understanding of the Islamic capital market and people's interest in investing in the Islamic capital market in South Sulawesi, which is reviewed in four indicators consisting of (1) products, (2) security or risk (3) mechanisms, ( 4) interests. This research uses quantitative methods with online surveys in the form of questionnaires through websites, email and social media. The research sample was 232 respondents. The results of the study, (1) public understanding of investment and product variations in the Islamic capital market is sufficient to understand, (2) understanding of the safety or risk of the community and the benefits of investing in the Islamic capital market are very good, (3) public understanding of the mechanism and opening of accounts in the Islamic capital market it is lacking as a mechanism and procedure for opening accounts in the Islamic capital market. (4) Public interest in South Sulawesi is very large to advance investment in the Islamic capital market. This research provides information about Indonesian securities, publishers and stock exchanges to intensify education to the community, especially in the province of South Sulawesi.